2015
DOI: 10.1186/s13023-015-0262-5
|View full text |Cite
|
Sign up to set email alerts
|

Pressure for drug development in lysosomal storage disorders – a quantitative analysis thirty years beyond the US orphan drug act

Abstract: BackgroundLysosomal storage disorders are a heterogeneous group of approximately 50 monogenically inherited orphan conditions. A defect leads to the storage of complex molecules in the lysosome, and patients develop a complex multisystemic phenotype of high morbidity often associated with premature death. More than 30 years ago the Orphan Drug Act of 1983 passed the United States legislation intended to facilitate the development of drugs for rare disorders.We directed our efforts in assessing which lysosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 19 publications
0
53
0
1
Order By: Relevance
“…Velmanase alfa is currently licensed in the European Union “for patients with mild to moderate alpha‐mannosidosis for treating effects of the disease that do not involve the brain (non‐neurological effects)” (https://www.ema.europa.eu/en/medicines/human/EPAR/lamzede). This drug labeling acknowledges that enzyme replacement therapy does not cross the blood‐brain barrier and would not be expected to cure the neurological disease associate with alpha‐mannosidosis, which may result in incomplete treatment of CNS manifestations. In addition, there might be various levels of yet‐to‐be defined “limited window of opportunity for early intervention” which might result either in prevention, disease stability, or reversibility, or modifying morbidity and premature mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Velmanase alfa is currently licensed in the European Union “for patients with mild to moderate alpha‐mannosidosis for treating effects of the disease that do not involve the brain (non‐neurological effects)” (https://www.ema.europa.eu/en/medicines/human/EPAR/lamzede). This drug labeling acknowledges that enzyme replacement therapy does not cross the blood‐brain barrier and would not be expected to cure the neurological disease associate with alpha‐mannosidosis, which may result in incomplete treatment of CNS manifestations. In addition, there might be various levels of yet‐to‐be defined “limited window of opportunity for early intervention” which might result either in prevention, disease stability, or reversibility, or modifying morbidity and premature mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the constant debate surrounding this issue, the success of such legislation in driving drug development for LDs must not be undermined. However, even with these incentives, LDs with a very low incidence or those that display primarily neurological symptoms, which are currently untreatable, have been faced with a low “development pressure”, probably due to a lower chance of success [64]. …”
Section: Lysosomes and Lysosomal Storage Disordersmentioning
confidence: 99%
“…Second, more prevalent orphan diseases may be more likely to be depicted in a TV series. Previous literature has shown that an orphan drug development is more likely in the more prevalent orphan diseases [48]. Third, the real benefit of such "product placement" is questionable as orphan drugs will only be of therapeutic interest for a very small portion of the television series' viewership.…”
Section: Discussionmentioning
confidence: 99%